2013
DOI: 10.1038/nmeth.2519
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of phosphorylation and ubiquitylation cross-talk in protein degradation

Abstract: Crosstalk between different types of post-translational modifications (PTMs) on the same protein molecule adds specificity and combinatorial logic to signal processing, but has not been characterized on a large-scale basis. Here, we developed two methods to identify protein isoforms that are both phosphorylated and ubiquitylated in the yeast Saccharomyces cerevisiae, identifying 466 proteins with 2,100 phosphorylation sites co-occurring with 2,189 ubiquitylation sites. We applied these methods quantitatively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
532
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(570 citation statements)
references
References 47 publications
34
532
0
4
Order By: Relevance
“…Ubiquitylation plays a prominent role in hexose transporters degradation (Horak and Wolf, 1997; Nijland et al, 2016; Roy et al, 2014), whereas phosphorylation is the primary mechanism for regulating cellular signaling (Humphrey et al, 2015). However, distinct phosphorylation sites are often used in conjunction with ubiquitylation in degradation, and these distinct sites are more highly conserved than the entire set of phosphorylation sites (Swaney et al, 2013). Hxt2 can be ubiquitinated at residue K26 and this triggers its inactivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ubiquitylation plays a prominent role in hexose transporters degradation (Horak and Wolf, 1997; Nijland et al, 2016; Roy et al, 2014), whereas phosphorylation is the primary mechanism for regulating cellular signaling (Humphrey et al, 2015). However, distinct phosphorylation sites are often used in conjunction with ubiquitylation in degradation, and these distinct sites are more highly conserved than the entire set of phosphorylation sites (Swaney et al, 2013). Hxt2 can be ubiquitinated at residue K26 and this triggers its inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, transcription of these genes is repressed at high glucose concentration, while under those conditions, Hxt2 and Hxt7 proteins at the membrane are targeted to the vacuole for degradation (Kruckeberg et al, 1999; Ye et al, 2001). Hxt7 and Hxt2 can be ubiquitinated and phosphorylated at N‐terminal residues (Swaney et al, 2013) and this likely contributes to their degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the interplay between phosphorylation and lysine acetylation was systematically investigated by the deletion perturbations in the Mycoplasma pneumonia genome (21). The relationship between phosphorylation and ubiquitylation was studied after proteasome inhibition on Saccharomyces cerevisiae (22). These studies suggested that crosstalks between different PTMs were extensive and remained to be discovered.…”
mentioning
confidence: 99%
“…The interplay between two PTMs was studied in both prokaryote and eukaryote [127,128], which suggested that cross-talk between different PTMs was extensive and remained to be discovered. The large-scale PTM proteomics data revealed that PTM cross-talk may also exist in cyanobacteria since many proteins were discovered to have more than one PTM [23,25,27].…”
Section: Challenge and Perspective In Ptm Proteomics Of Cyanobacteriamentioning
confidence: 99%